Infant mortality and the Notification of Births Acts, 1907, 1915 - Lawson, William (Statistical and Social Inquiry Society of Ireland, 1919)
This subject was referred to in a paper on "Child Life as a National Asset," read before the Society by Mr. Shannon Millin on December 17th, 1915, but as a good deal of information on the subject was forthcoming from England and Scotland, which might assist the working of the Notification of Births Acts in Ireland, and throw light on the methods adopted for the protection of Infant Life, I was asked to give the Society the benefit of my investigations.
President's address
Read November 15th, 1917
Keywords: Registration of births; Infant mortality; 314.15